Revisiting oxidative stress and mitochondrial dysfunction in the pathogenesis of Parkinson disease-resemblance to the effect of amphetamine drugs of abuse - Perfeito, Rita (2012)
Parkinson disease (PD) is a chronic and progressive neurological disease associated with a loss of dopaminergic neurons. In most cases the disease is sporadic but genetically inherited cases also exist. One of the major pathological features of PD is the presence of aggregates that localize in neuronal cytoplasm as Lewy bodies, mainly composed of α-synuclein (α-syn) and ubiquitin. The selective degeneration of dopaminergic neurons suggests that dopamine itself may contribute to the neurodegenerative process in PD. Furthermore, mitochondrial dysfunction and oxidative stress constitute key pathogenic events of this disorder. Thus, in this review we give an actual perspective to classical pathways involving these two mechanisms of neurodegeneration, including the role of dopamine in sporadic and familial PD, as well as in the case of abuse of amphetamine-type drugs. Mutations in genes related to familial PD causing autosomal dominant or recessive forms may also have crucial effects on mitochondrial morphology, function, and oxidative stress. Environmental factors, such as MPTP and rotenone, have been reported to induce selective degeneration of the nigrostriatal pathways leading to α-syn-positive inclusions, possibly by inhibiting mitochondrial complex I of the respiratory chain and subsequently increasing oxidative stress. Recently, increased risk for PD was found in amphetamine users. Amphetamine drugs have effects similar to those of other environmental factors for PD, because long-term exposure to these drugs leads to dopamine depletion. Moreover, amphetamine neurotoxicity involves α-syn aggregation, mitochondrial dysfunction, and oxidative stress. Therefore, dopamine and related oxidative stress, as well as mitochondrial dysfunction, seem to be common links between PD and amphetamine neurotoxicity.